2014
DOI: 10.1037/a0035619
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of affective instability in patients with borderline personality disorder compared to posttraumatic stress disorder, bulimia nervosa, and healthy controls.

Abstract: Affective instability is a core feature of borderline personality disorder (BPD). The use of advanced assessment methodologies and appropriate statistical analyses has led to consistent findings that indicate a heightened instability in patients with BPD compared with healthy controls. However, few studies have investigated the specificity of affective instability among patients with BPD with regard to relevant clinical control groups. In this study, 43 patients with BPD, 28 patients with posttraumatic stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
160
7
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(178 citation statements)
references
References 72 publications
9
160
7
2
Order By: Relevance
“…These findings are in line with the conclusion formulated by Houben, Van Den Noortgate et al (2015), in which was shown that several indicators of emotional change were not specifically linked to BPD, as other clinical groups or other indicators of psychological ill-being were characterized by similar patterns. Moreover, the results show that next to limited specificity for indicators of changes in the overall intensity of emotions as concluded in Santangelo, Reinhard et al (2014), also indicators of emotional switching between positive and negative emotions are not very specific to BPD after comparison with other clinical groups.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…These findings are in line with the conclusion formulated by Houben, Van Den Noortgate et al (2015), in which was shown that several indicators of emotional change were not specifically linked to BPD, as other clinical groups or other indicators of psychological ill-being were characterized by similar patterns. Moreover, the results show that next to limited specificity for indicators of changes in the overall intensity of emotions as concluded in Santangelo, Reinhard et al (2014), also indicators of emotional switching between positive and negative emotions are not very specific to BPD after comparison with other clinical groups.…”
Section: Discussionmentioning
confidence: 78%
“…We used two datasets in which previously it was shown that BPD patients tend to show large changes in overall emotional intensity over time in daily life (Santangelo, Reinhard et al, 2014 and Scheiderer et al, 2015). However, these emotional intensity results were not always specific to BPD after comparison with other clinical groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These momentary ratings were used to derive the Mean Squared Successive Difference (MSSD) statistic, calculated as the squared difference across successive time points in relation to the distance between the measured time points. Consistent with prior research in samples with various forms of psychopathology, including eating disorders, (e.g., Santangelo et al, 2014; Woyshville et al, 1999), this statistic was used as an EMA-based measure affect lability, as it represents the extent to which consecutive negative affect ratings vary across time points. Finally, participants were instructed to report the occurrence of each episode of binge eating and self-induced vomiting, and were also given the opportunity at each random signal to report recent behaviors (i.e., those that had occurred since their last recording) that they had not previously reported.…”
Section: Methodsmentioning
confidence: 99%